Retrospective analysis of cancer morbidity among patients after computed tomography - M. V. Osipov; V. Yu. Shkarednykh; V. S. Loginov; V. V. Melnikov; P. S. Druzhinina; M. E. Sokolnikov (Радиационная гигиена, 2021)
Cancer morbidity among patients examined using computed tomography within 10 years follow-up period depending on various factors has been retrospectively analyzed. Information on Ozyorsk residents examined at the Kasli District Hospital was retrospectively collected. The data collection period started in 2009 when the first computed tomography examination has been performed in the X-ray department of Kasli District Hospital, and ended by December 31, 2018. The data obtained in the study were linked to the local Cancer registry, the Death registry, and the “CT Registry” database to receive information about the vital status, cancer morbidity and CT examinations performed outside the Kasli District Hospital. Cumulative incidence has been accounted in terms of predisposed conditions associated with cancer, cancer diagnoses stated before the date of the first CT examination and CT-confirmed malignancy cases. As a result of the study, information on 275 examinations of 246 residents of the Ozyorsk urban district has been derived. By the end of the observation period, 46 cases of malignant tumors were accumulated in the study group. The average time from 1st CT to the end of follow-up was 6.5 years. The distribution of carcinogenic effects among patients examined using CT has been shown retrospectively from the date of birth to the date of the end of follow-up. The cumulative cancer incidence adjusted for predisposing conditions has been compared with the LSS data. No epidemiological data were found on the relationship between the detected cases of malignant tumors and the diagnostic radiation from CT scans. The data obtained in the study provide information on the long-term oncological effects among Ozyorsk residents examined using CT as a source of additional information for a comprehensive assessment of the low dose effects associated with diagnostic exposure in the Ozyorsk Computed Tomography Cohort study.